Synthesis and Characterization of Chitosan Nanoparticles from theshells of crabs(Portunus pelagicus) and Application as Antimicrobial - Fatahu Fatahu; Hasnah Natsir; Paulina Taba (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2015)
Chitosan was modified into nanoparticle chitosan in order to increase its absorptivity and solubility in water so that it can be applied in various fields. The objective of this research was to produce nanometer-sized chitosan, to characterizethe functional groups and the particle size of chitosan  as  well  as  to  test  its  antimicrobial  activity.  Chitosan  nanoparticles  were  synthesized through ionic gelation method by reacting chitosan with tripolyphosphate ions through ionic cross- linking reaction. The functional groups of chitosan were determined from its FTIR spectrum, the particle size was obtained from its X-ray diffractogram  and particle size analysis (PSA). Chitosan nanoparticles  with  the  smallest  size  based  on  XRD wereobtained  at  a  concentration  of  0.1% chitosan (CNPs 1) and chitosan 0.2% (CNPs 2) with the addition of 0.1 % tripolyphosphate ion. The sizes of chitosan nanoparticles,CNPs 1 and CNPs 2,obtained from the analysis of PSA were 224.68 and 204.32 nm, respectively. Polydisperse index value (pdi) of chitosan nanoparticles produced  were  0.226  and  0.261  (pdi  <0.5),  respectively.  The  results  indicate  that  chitosannanoparticles synthesized havehomogeneous particle size distributions. The test results against four types of pathogens showed that CNPs 2 had inhibitory activity against the three types of microbes, Staphylococcus aureus, Pseudomonas aeruginosa, and Malassezia furfur, but it was not active against the fungus of Candida albicans.